An Analysis of Social Class Dynamics in The Film House Of Gucci (2021) - Andriani, Nia; Putra, Dhanu Ario; Diana, Eli (Jurnal Penelitian Multidisiplin Bangsa, 2025)
This research discuss the dynamics of social class in the film House of Gucci (2021) using Karl Marx's theory and Kurt Lewin's theory of social change. This research aims to find out how social class is depicted in the film, especially the upper class (bourgeois) and lower class (proletariat), and how the characters experience social change. The method used is descriptive qualitative by analyzing several important scenes in the film. The results show that there are clear differences between social classes, both in terms of power and lifestyle. In addition, the characters in the film also experience a social change process shown through the unfreezing, changing, and refreezing stages. In this study, 11 scenes were found that represent social class dynamics, consisting of 7 scenes depicting the bourgeois class and 4 scenes depicting the proletarian class. Meanwhile, the analysis of social change shows that there are 3 scenes in the unfreezing stage, 7 scenes in the changing stage, and 1 scenes in the refreezing stage. This research is expected to help readers understand how films can reflect social issues that exist in real life.